Newly validated stability-indicating ultra-performance liquid chromatography-tandem mass spectrometry method for the estimation of Ceftaroline Fosamil by using a quadrupole mass detector - Jabeen, Bangalore Venkatappa Suma (Journal of Applied Pharmaceutical Science, 2022)
The present study aims to develop and validate a stability-indicating assay method to determine Ceftaroline Fosamil by using a hyphenated technique ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) in Active Pharmaceutical Ingredient (API) and dosage form. An Acquity C18 UPLC Bridged Ethyl Hybrid (BEH) (50 × 2.1 mm, 1.7 µm) analytical column coupled to a triple quadrupole mass detector was used. The isocratic elution was employed with acetonitrile and 0.1% formic acid in water in a 70:30 v/v ratio as the mobile phase. Mobile phase flow rate and column temperature were maintained at 0.35 ml/minute and 30°C, respectively, with an injection volume of 5 μl and runtime of 3 minutes. Positive electrospray ionization in Multiple reaction monitoring (MRM) mode was maintained. Ceftaroline Fosamil showed good resolution with a retention time of 0.91 ± 0.04 minute and was quantified at the transition pair m/z 685.30 → 208.10. The Limit of Detection (LOD) and Limit of Quantification (LOQ) were found to be 30 and 100 ng/ml, respectively. In the forced degradation studies, it was observed that Ceftaroline Fosamil was stable in all the stress conditions except in the basic medium. A UPLC-MS/MS analytical method was developed and validated along with stability studies in accordance with the International Council for Harmonisation (of Technical Requirements for Pharmaceuticals for Human Use) (ICH) guidelines to determine Ceftaroline Fosamil in the parental dosage form and API.
Keywords: Antibiotic, Ceftaroline Fosamil, cephalosporin, stability studies, UPLC-MS/ MS, ICH guidelines